On thin ice: reducing choking in elite ice hockey - Huard Pelletier, V. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
In their quest to be successful in major sport competitions, sport federations` stakeholders must master the aspects that lead to efficient selection procedures. However, the players who perform best in physical tests or intra-team games are not necessarily the ones who will perform best in big games when the pressure is on. In fact, the predisposition to perform at the right time becomes an important variable. Frequently used in popular culture, the concept of player`s choking susceptibility is an emerging construct in the domain of applied sport psychology. Choking is defined in the scientific literature as a significant decrease in performance in a competitive pressure situation, which is attributed to an increase in anxiety and when the athlete recognizes that the standards they have set for themselves would otherwise be met (Mesagno, 2013). To date, a few interventions have been conducted to attempt to reduce choking, but few studies have focused on team sports at the elite level. The purpose of this study is to measure the impact of sports psychology intervention aimed at preparing to perform optimally (by reducing choking susceptibility) among athletes representing their province at the 2023 Canada Games, in the discipline of ice hockey. The initial measurement for choking susceptibility of male (N=22 M age =15) and female (N=22, M age=17) athletes was done 6-months before the competition according to the calculation established by Mesagno (2008), then the anxiety state was measured during a minor competition 2 months later, and 1-week previously to competition. One month prior to the Games, 3 sessions, which consists of sports psychology conferences as well as individual consultations were offered to the athletes of both teams. Results reveal that athletes identified as susceptible to choking vary greatly in their level of on-ice performance, and that the interventions appear to have had a modest effect on player performance at major sporting events such as the Canada Games. In consideration of the results, alternatives will be proposed for future interventions in team sports with adolescents who evolve in highly competitive ice hockey settings. In addition, comments will be made on the measurement of the pressure choking concept and on the experience of the practitioners who participated in the study.